Structure and Raman Spectra of C60 and C70 Fullerenes Encased into Single-Walled Boron Nitride Nanotubes: A Theoretical Study - Brahim Fakrach; Fatima Fergani; Mourad Boutahir; Abdelhai Rahmani; Hassane Chadli; Patrick Hermet; Abdelali Rahmani (Crystals, 2018)
We report the structures and the nonresonant Raman spectra of hybrid systems composed of carbon fullerenes ( C 60 and C 70 ) encased within single walled boron nitride nanotube. The optimal structure of these systems are derived from total energy minimization using a convenient Lennard-Jones expression of the van der Waals intermolecular potential. The Raman spectra have been calculated as a function of nanotube diameter and fullerene concentration using the bond polarizability model combined with the spectral moment method. These results should be useful for the interpretation of the experimental Raman spectra of boron nitride nanotubes encasing C 60 and C 70 fullerenes.